Modeling and simulation of a diesel engine cooling system with the aim of controlling its temperature and reducing electrical energy consumption and emissions - ليلى علاء; نبيل غدير (Latakia University Journal -Engineering Sciences Series, 2024)
Advanced thermal management systems for internal combustion engines can regulate coolant temperature, consume less engine power, and positively impact environmental gas emissions and fuel economy by replacing conventional components with electrical actuators that can be controlled and operate in harmony with each other. In this paper, a computer simulation model of a diesel engine cooling system was prepared. Initially, a mathematical model was developed that describes the heat transfer within the cooling system. In the next stage, a non-linear control algorithm based on Lyapunov stability was developed in an attempt to track the engine temperature and maintain the engine temperature. Required and reducing the electrical energy consumed by the system’s operators. Computer programming was done using the MATLAB language to verify the proposed control algorithm with the aim of arriving at and analyzing the results and graphs. Thus, the engine temperature can be adjusted and kept within the optimal range, and this will reduce energy consumption and emissions and extend the life of the engine.